'Power to the reader' or 'degradation of literary taste'? Professional critics and Amazon customers as reviewers of The Inheritance of Loss. (August 2016) - Allington, Daniel
The Inheritance of Loss by Kiran Desai (2006) was critically lauded, gaining many positive periodical reviews and winning both the Man Booker Prize and the National Book Critics Circle Award for Fiction. However, it has received mixed reviews from customers of the online retail giant, Amazon: an arguable expression of the challenge that digital consumerism presents to literature's longstanding claim to autonomy from the market. In order to understand the relationship between the book's professional and customer reviews, a collection comprising both was constructed. Qualitative analysis of these reviews was followed by the use of thematic coding to compare sub-collections divided by means of publication and by geographical location, with social network graphs being used to represent similarities between reviews and graph density being employed as a measure of overall similarity. No distinctions were found between reviews when grouped according to geographical location. However, the novel's professionally published reviews were found to be a more homogeneous group than its Amazon customer reviews, and to be more likely to recommend the novel and to praise it for its humour and its narrative, while customer reviews were found to be more likely to criticise it for its characters, and less likely to quote it or to discuss its political themes. It is argued that this is because the book was produced to satisfy the expectations of a 'literary' rather than a 'popular' audience, where professional book reviewers represent the former almost by definition.